ANALYSIS OF TEACHER ABILITIES IN IMPLEMENTING ONLINE LEARNING IN ELEMENTARY SCHOOLS OF THE NORTH SUMATRA PAB FOUNDATION - Yusrizal Yusrizal; Fatmawati Fatmawati (Jurnal Ilmiah Teunuleh, 2020)
This study aims to describe the ability of teachers to implement online learning in private primary schools in North Sumatra PAB. The method used in this research is a quantitative method with a descriptive research type. Descriptive research in this study aims to describe the observed data. The population in this study were 31 schools in North Sumatra PAB private primary schools. The sampling technique in this study was random sampling, while the sample in this study was 9 schools with each school being taken by one teacher as the research sample. The data collection technique in this research is observation. The data analysis technique is using the descriptive data analysis technique. Based on the results of the study, it can be concluded that: the teacher's ability to implement online learning in North Sumatra PAB primary schools is low. The low ability of teachers is caused by several factors, but in this study the biggest factor is the lack of teacher motivation in learning technology, which causes online learning not to be carried out as expected. Therefore, the government's attention to the mastery of technology for all teachers is something that needs to be improved considering that one of the biggest indicators of the times is the rapid development of technology.